2016
DOI: 10.1371/journal.pone.0156201
|View full text |Cite
|
Sign up to set email alerts
|

Acclimatization of Photosynthetic Apparatus of Tor Grass (Brachypodium pinnatum) during Expansion

Abstract: The aim of this study was to understand the acclimatization mechanisms of photosynthetic apparatus in Brachypodium pinnatum (L.) P. Beauv grass during its expansion. Twelve populations differentiated by age: young (30–50 years old), intermediate age (ca. 100 y) and old (>300 y) were studied. It was confirmed that the decrease of the number of genotypes as a result of environmental stress and competition were reflected in changes in chlorophyll fluorescence (ChlF) parameters. The old stands were dominated by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 68 publications
1
23
0
Order By: Relevance
“…The lower JIP curve in Hysun-33 and Hysun-39 indicated the accumulation of inactive reaction centers of PSII as compared to S.28111 and SF0049 under combined stress. Insignificant changes at 'O' step indicated that there was a little or no loss of energy transfer to reaction centers from antenna complex (Baker 2008). This may be due to higher number of inactive reaction centers (lower peak) where electrons cannot be transferred from reduced plastoquinone (QA -) or LHCII to PSII core (Murkowski 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower JIP curve in Hysun-33 and Hysun-39 indicated the accumulation of inactive reaction centers of PSII as compared to S.28111 and SF0049 under combined stress. Insignificant changes at 'O' step indicated that there was a little or no loss of energy transfer to reaction centers from antenna complex (Baker 2008). This may be due to higher number of inactive reaction centers (lower peak) where electrons cannot be transferred from reduced plastoquinone (QA -) or LHCII to PSII core (Murkowski 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It was expected that Chl fluorescence can be used for a fast assessment of cultivar acclimatization and can be helpful in management and planning (Bąba et al 2016). The common effects of combined salt and drought stresses on growth and development of oil seed crop plants, such as sunflower and soybean, have been reported but their photochemical efficiency through Chl a fluorescence is not well established.…”
Section: Introductionmentioning
confidence: 99%
“…This method is also suitable for continuous real-time in-situ monitoring. JIP-test parameters gave much information on plant performance when applied in field conditions in agriculture and horticulture (Tsonev et al 2011, Swoczyna et al 2019, forestry (Pollastrini et al 2014, Bussotti andPollastrini 2015), urban environment (Hermans et al 2003, Ugolini et al 2012, Swoczyna et al 2015, ecological research (Bąba et al 2016), etc.…”
Section: Introductionmentioning
confidence: 99%
“…The changes in fluorescence signals are related, directly or indirectly, to various stages of photosynthetic light reactions: photolysis of water, reduction of photosynthetic machinery components, electron transport, generation of the pH gradient across thylakoid membranes, and ATP synthesis (Goltsev et al 2016, Kalaji et al 2017a. The technique based on detailed analysis of Chl a fluorescence signals is known as JIP-test (Strasser et al 2004), which is frequently used to study the changes in structure and function of photosynthetic apparatus (Kautsky and Hirsch 1931, Stirbet and Govindjee 2011, Kalaji et al 2014aChen et al 2015, Bąba et al 2016, Kalaji et al 2017a. Illumination of dark-adapted leaf tissue leads to an increase of a prompt Chl fluorescence (PF) signal, which curves are named as chlorophyll fluorescence induction curves.…”
Section: Introductionmentioning
confidence: 99%